White adolescents' racial contexts: Associations with critical action. Issue 6 (17th June 2022) - Dull, Brandon D.; Hoyt, Lindsay Till; Chaku, Natasha
Abstract: This study takes a person‐centered approach to investigate White youths' racial contexts by utilizing a latent profile analysis among a sample of White adolescents ( N = 323, ages 16–17; 52% female, 48% male; data collected 1996–1998). Racial contexts were composed of parent, peer, and school influences, which revealed three distinct profiles: a Race Conscious profile, a Race Silent profile, and a Low Race Engagement profile. These profiles predicted White adolescents' critical action during emerging adulthood, where adolescents in the Race Conscious profile were engaged in more critical action as compared to the other two profiles. These findings suggest that the racial contexts in which White adolescents develop have direct implications on their desire to work toward, and take action for, social change.